New fermions in the light of the (g − 2)μ - Djouadi, A.; Criado, J.C.; Koivunen, N.; Müürsepp, K.; Raidal, M.; Veermäe, H. (Frontiers in Physics, 2022)
The very precise measurement of the anomalous magnetic moment of the muon, recently released by the Muon g-2 experiment at Fermilab, can serve to set stringent constraints on new particles. If the observed 4σ discrepancy from the Standard Model value is indeed real, it will set a tight margin on the scale of the masses and couplings of these particles. Instead, if the discrepancy is simply a result of additional theoretical and experimental uncertainties to be included, strong constraints can be put on their parameters. In this mini-review, we summarize the impact of the latest muon g-2 measurement on new fermions that are predicted by a wide range of new physics models and with exotic quantum numbers and interactions. We will particularly discuss the case of vector-like leptons, excited leptons, and supersymmetric fermions, as well as spin-3/2 isosinglet fermions, which have been advocated recently.